2023
DOI: 10.1038/s41398-023-02523-1
|View full text |Cite|
|
Sign up to set email alerts
|

Plasma concentrations of lysophosphatidic acid and the expression of its receptors in peripheral blood mononuclear cells are altered in patients with cocaine use disorders

Abstract: We have recently reported alterations in the plasma concentrations of lysophosphatidic acid (LPA) in patients with substance use disorders. In order to further explore the potential role of the LPA signaling system as biomarker in cocaine use disorders (CUD) we conducted a cross-sectional study with 105 patients diagnosed with CUD and 92 healthy controls. Participants were clinically evaluated and blood samples were collected to determine plasma concentrations of total LPA and LPA species (16:0-, 18:0-, 18:1-,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 46 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…Thus, LPA receptors have been implicated in neurodevelopmental and neuropsychiatric diseases such as neuropathic pain, ischemic stroke, traumatic brain injury, spinal cord injury, fetal hypoxia, fetal hydrocephalus, schizophrenia and Alzheimer disease [22,27]. Furthermore, sex differences in all LPA species unless for LPA 18:0 and 18:1 have been found in previous studies revealing a robust sexual dimorphism [23,28,29]. On the other hand, because the activation of the LPA receptor has been involved with the release of neurotransmitters (e.g., dopamine) associated with behavior, reward and learning and memory processes, it has been suggested to be implicated in substance use disorders [30][31][32][33].…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…Thus, LPA receptors have been implicated in neurodevelopmental and neuropsychiatric diseases such as neuropathic pain, ischemic stroke, traumatic brain injury, spinal cord injury, fetal hypoxia, fetal hydrocephalus, schizophrenia and Alzheimer disease [22,27]. Furthermore, sex differences in all LPA species unless for LPA 18:0 and 18:1 have been found in previous studies revealing a robust sexual dimorphism [23,28,29]. On the other hand, because the activation of the LPA receptor has been involved with the release of neurotransmitters (e.g., dopamine) associated with behavior, reward and learning and memory processes, it has been suggested to be implicated in substance use disorders [30][31][32][33].…”
Section: Introductionmentioning
confidence: 74%
“…Recently, studies in rats showed that plasma levels of total LPA were lower after 30 min of acute and chronic cocaine administration (5 mg/kg for males and 30 mg/kg for females). In addition, total LPA concentrations were lower before 72 h of abstinence in male rats that were exposed to 15 mg/kg every day for two weeks, but abstinence had no impact on total LPA levels in females rats [29]. In contrast, intracerebroventricular infusions of LPA in mice might increase adult-hippocampal neurogenesis that enhances forgetting of cocaineassociated contextual memories [48].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations